2013
DOI: 10.1007/s00520-013-1887-3
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of skeletal-related events in patients with breast, lung, or prostate cancer and metastases to bone: a 15-year study in two large US health systems

Abstract: SREs are a frequent complication in patients with solid tumors and bone metastases, and are much more common than previously recognized in women with BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 25 publications
5
105
0
3
Order By: Relevance
“…These findings are similar to those of a previous Japanese study [3]. Although the incidence of SREs in patients with PCa in the present study was low compared to that observed in a previous large multicenter study [1, 4] (38–51.7%), the incidence of SREs in patients with RCC was similar to that found in a previous study [5] (72%). It is not clear why the incidence of SREs in patients with PCa was lower in a Japanese cohort than the incidence observed in European or American countries.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings are similar to those of a previous Japanese study [3]. Although the incidence of SREs in patients with PCa in the present study was low compared to that observed in a previous large multicenter study [1, 4] (38–51.7%), the incidence of SREs in patients with RCC was similar to that found in a previous study [5] (72%). It is not clear why the incidence of SREs in patients with PCa was lower in a Japanese cohort than the incidence observed in European or American countries.…”
Section: Discussionsupporting
confidence: 77%
“…SREs include pathological fractures, spinal cord compression, need for bone palliative radiotherapy/surgical intervention, and hypercalcemia. The incidence of SREs in prostate cancer (PCa), renal cell carcinoma (RCC), and urothelial carcinoma (UC) with bone metastasis is high, with previous publications reporting rates of 29–51.7% [1-4], 72–82% [3, 5], and 65–68% [3, 6], respectively. However, there have been few studies comparing clinical information and risk factors related to SREs in GU cancers with bone metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Oster és mtsai [20] 723 prostatacarcinomás betegének egyéves átlag-túlélése 73% volt, míg ugyanez az érték Weiss és mtsai [21] beteganyagában (306 beteg), ahol már műtétet indokló csontáttétek jelentek meg, már 29%-ra csökkent. Szintén csökkenti a túlélést, ha a csontáttétes beteg 70 év feletti, nagyszámú csont-, illetve visceralis áttéttel rendelkezik, magas a szérum-alkalikusfoszfatáz értéke és ha az androgének megvonására igen magas PSA-értékek alakulnak ki [22].…”
Section: Prognosztikai Faktorok éS Diagnosztikai Algoritmus Jelentőséunclassified
“…Szelektálatlan, azaz mindenfajta tumor csontmetasztázi-sát magába foglaló közlemények egyéves túlélése 39-54% között mozgott [2,8,[25][26][27], ami alacsonyabbnak bizonyult az emlő-vagy veseráknál észlelteknél [11, 12, 14, 18-20, 28, 29], de nem meglepő módon lényegesen meghaladta a tüdőrákok egyéves túlélési eredményeit [20,30,31]. Az emlő-és veserákok 45-58%-os egyéves biztató túlélési eredményei azonban az első öt év végére már mindössze 8-20%-ra csökkentek [11,14,19,28].…”
Section: Prognosztikai Faktorok éS Diagnosztikai Algoritmus Jelentőséunclassified
“…In a recent meta-analysis, the median survival time of patients with castration-resistant prostate cancer and bone metastases was 21.3 months (3). In a 15-year study from the USA, more than half of patients with bone metastases from prostate cancer had evidence of SREs, either at diagnosis of bone metastases or subsequently (4).…”
Section: Introductionmentioning
confidence: 99%